Pengembangan Proses Bisnis dan Rancangan Aplikasi Sistem Informasi Penerimaan dan Penilaian Peserta Co - Ass pada RSUD - Yanti Yanti; Yunita Fransisca; Jacklyn Suwargo (ComTech: Computer, Mathematics and Engineering Applications, 2013)
This study aims to is to explore the admission process and assessment of participant Co – Assistant doctor on a regional hospital which is still performed manually, to identify problems encountered and required information in the development of Information Systems of Participants Acceptance and Assessment of Co – Assistant doctor, and design the information System . Methods used are literature study, data collection (observation and interviews), analysis, and design. This study results in a computerized information systems of acceptance and assessment of Co - Ass participant  to improve the quality of service from the Human Resources division. Creating the required reports assists the Head of HR to determine the performance of Co - Ass. In addition, the design of information systems  reduces the possibility of data losses and documents recording errors made by the Executive Training Unit, and assist the hospital management in confirming the existing organizational structure and its duty of each division to provide document creation system and authorization by the external parties.